Determinan Atas Kinerja Keuangan Perusahaan Telekomunikasi Di Indonesia - Eneng Sugihyanty (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2018)
This study aims to analyze the effect of exchange rates, inflation, interest rates and stock prices on financial performance. Based on the test results of stock prices testing of the partial variables have positive and significant to the variable financial performance. For variable exchange rates, inflation, interest rates have not positive to the variable financial performance. This means that stock prices are the variable that better assess financial performance of telecommunication company. The results of this study it is expected that the variable exchange rates, inflation, interest rates and stock prices can be a guide, either by the management company in the management of the company, as well as by investors in determining investment strategy.